(untitled) (Jahangirnagar University Journal of Biological Sciences, 2024)
Setipinna phasa is known as Phasha maach, a common fish in Bangladesh popular as sutki (dried fish). Since Bangladesh exports a significant amount of dried fish to other countries, this study was conducted to find out the fungus associated with the dried fish as well as its morphological characteristics, cultural factors and molecular identification. Aspergillus ochraceopetaliformis was isolated from Setipinnaphasa and identified by analysis of mycelium and conidia morphologyas well as by analysis of the internal transcribed spacer region (ITS) of Aspergillus ochraceopetaliformis PCR products measuring 606 bp and a blast search revealed 99% sequence similarity to the Aspergillus ochraceopetaliformis species complex. Analysis of the pathogen’s vegetative growth characteristics revealed that Hennerberg media (22mm) and yeast extract mannitol media (12mm), had, on average, the highest and lowest mycelial growth rates, respectively. The optimal pH and temperature for mycelial growth of Aspergillus ochraceopetaliformis were 7 and 30˚C, respectively. To the best of our knowledge, this finding of Aspergillus ochraceopetaliformis from Setipinna phasa is the first-ever work in Bangladesh. Jahangirnagar University J. Biol. Sci. 12(1 & 2): 87-95, 2023 (June & December)